The Apparent Lack of the Risk of Intussusception Immediately After Rotavirus Vaccination Among Japanese Infants - Wakako Kikuchi; Atsuko Noguchi; Yoko Sato; Yuuki Konno; Akira Komatsu; Satoru Tandai; Wataru Kikuchi; Shinobu Miura; Hiroshi Fukaya; Tomoaki Ohata; Hiroo Noguchi; Kenichi Matsuno; et al. (Viruses)
Rotavirus vaccines carry a small risk of intussusception mainly 1–7 days after vaccination in the United States of America, Europe, Australia, and Latin America where the background rate of intussusception is relatively low. Such risks are undetectable in Africa and India where the background rate is the lowest. Because few studies were carried out in high-background-rate countries such as Japan, we examined how intussusception occurred in infants living in Akita prefecture, Japan, while the vaccines were sold in the private market. Between 2011 and 2018, an estimated 21,677 infants (46%) were vaccinated and 54% were not. Through a retrospective survey of medical records in 18 hospitals in the prefecture, we identified 58 infants, 28 of whom were vaccinated and 30 of whom were unvaccinated, as having intussusception that met level 1 of the Brighton criteria. Thus, the intussusception rate was 123 per 100,000 infant-years (95% confidence interval [CI]: 94–160). Despite the high rate, none developed intussusception 1–7 days after the first dose of either the monovalent human rotavirus vaccine (GSK) or the pentavalent human–bovine reassortant vaccine (MSD). The incidence rate ratio of vaccinated to unvaccinated infants between 42 and 245 days of life was estimated at 0.96 (95%CI: 0.43–2.1; p = 0.92). Given that over 95% of infants received the first dose before 15 weeks of age, the risk of intussusception associated with the rotavirus vaccines in high-incidence-rate countries can be reduced to a minimum by adhering to the recommended schedule at 2, 3, and 4 months of age.